HABITUS KEBERSIHAN DALAM PERSPEKTIF LIVING HADIS Studi Sosiologis atas Internalisasi Hadis al-Ṭuhūr di Pesantren Al-Ihsan Malang - Anis Nurma Sabila, Nasrulloh (JIPI (Jurnal Ilmiah Pendidikan Islam), 2026)
This study examines how the prophetic tradition (hadith) of al-ṭuhūr is actualized, internalized, and functions as symbolic capital in shaping the cleanliness habitus of students at Pesantren Al-Ihsan, Malang. Cleanliness practices in pesantren reflect a dialectic between Islamic ideals and students’ varying levels of awareness. Using a qualitative approach with a living hadith design and Pierre Bourdieu’s habitus theory, data were collected through participant observation, interviews, and document analysis. Findings show that the hadith is actualized through students’ normative understanding of cleanliness as part of faith, personal and communal practices, and reinforcement through social interaction. Internalization occurs through formal regulations, monitoring, exemplary behavior of teachers, and routine habituation. These mechanisms serve as symbolic capital that legitimizes and strengthens compliance. Continuous habituation produces stable dispositions, evident in students’ spontaneous cleanliness practices. The study concludes that the synergy between living hadith and habitus forms a circular process that sustains the hadith in daily pesantren life, highlighting pesantren as an effective arena for character formation.